The relationship between overjet size and dentoalveolar compensation - Soliman Nadia; El-Batran Mona; Abou-Zeid Ahmed; Sarry El-Din Azza; Zaki Moushira (Wolters Kluwer Medknow Publications, 2009)
Background : The purpose of this study was to investigate the effect of overjet size and the dento-alveolar compensation in subjects with normal class I molar relationship. Materials and Methods: Lateral cephalometric head records of 59 Egyptian children (34 boys and 25 girls) aged 7.5 to 10.5 years with mean age of 8.69±0.73. All had normal class I type of occlusion. The sample was classified into four quartiles according to the overjet size and the cephalometric analysis was based on seven linear and eight angular measurements using a dental tracer programme. Results: showed that, in spite of presence of high significant over jet size differences between the groups; there was no significant differences in all the studied parameters were found. Applying the least significant differences (LSD) test and coefficient correlations between the studied parameters clarifying that there was a significant differences in angular measurements (SN-AB, SN-Occl, I-I, I-ML, I-NB). Conclusion: during transitional dentition there was a sufficient dento-alveolar adaptation to growth changes in the saggittal jaw relation ship to attain normal class I type of occlusion. This compensation is pronounced in angular parameters and clustered in the lower arches particularly in incisal area.